South Asia and Africa after independence : post-colonialism in historical perspective - Waites, Bernard (Basingstoke, Hampshire : Palgrave Macmillan, 2012)
"The first single-volume comparative history of postcolonial South Asia and sub-Saharan Africa in the first generation since independence. Drawing together detailed economic and political analysis, Waites assesses the colonial impact on these regions, establishing breaks and continuities, and highlighting their diversity and interplay."--
Introduction: Post-colonialism in Historical Perspective -- Post-colonial Trajectories in South Asia -- Democracy, Economic Planning and Economic Stagnation in India: 1947-c.1975 -- Caste in post-colonial India -- Politics and Economics in Independent African States -- Nigeria and Congo-Zaire, 1960-c.1975: Decolonisation, Civil War and State Recovery -- Nigeria and Congo-Zaire from the 1970s to Late 1990s: Regional Giants, Giant Failures? -- Colonialism, Post-colonialism and Ethnic Violence: the Examples of Rwanda and Burundi --Angola and Mozambique.
Includes bibliographical references (p. 413-438) and index.
Keywords: Postcolonialism -- Africa, Sub-Saharan.; Postcolonialism -- South Asia; South Asia -- History -- 20th century; South Asia -- History -- 21st century; South Asia -- Politics and government -- 20th century; South Asia -- Politics and government -- 21st century; Africa, Sub-Saharan -- History -- 1960-; Africa, Sub-Saharan -- Politics and government -- 1960-